Conversion of biomass into bioenergy for a sustainable circular bioeconomy: potential solution to the environmental issues - Alam, Md Zahangir (Rajshahi University of Engineering & Technology (RUET), 2023)
The conversion of biomass into energy, also known as bioenergy, is the energy derived from biodegradable materials and is considered a potential solution to global energy problems. Concerning global sustainability, the reliance on fossil fuels and greenhouse gas emissions that contribute to global warming are particularly alarming. In order to address pressing issues and crises, an alternative and potentially viable solution is necessary. Currently, the most prevalent biomass feedstocks for energy conversion are plants, crops, and their wastes, which are potential resources and can be converted into biofuels, biopower, and a variety of bioproducts. The primary biomass sources in Malaysia are sewage treatment plant (STP) sludge managed by the Indah Water Konsortium (IWK), a national sewerage company, and oil palm industrial (OPI) wastes considered oil palm biomass (OPB) as well as abundant food waste generated daily. Current advanced research and development seeks an effective and efficient solution to biomass by converting waste to bioenergy, which could be a complete and viable solution with the generation of revenue and a circular economy approach at the point of generation for sustainable development. This keynote address provides an overview of the research on 'Turning waste into valuable bio-products,' with a focus on biofuels (bioethanol, biomethane and biogas) and bioenergy from the perspective of green technology. In Malaysia, various biofuels and bioenergy are currently being developed from a variety of domestic and industrial waste sources. The sources and characteristics of various biomass feedstocks in Malaysia are to be discussed. The topic discusses how data from research and development (R&D) could be scaled up to the commercial level for the recovery of renewable energy using green technology. For sustainable development, certain case studies on the bioconversion of food waste, sewage sludge, and oil palm industry waste into biofuels and bioenergy are to be shared. In addition, some results are shared on the investigation of the potential of food waste (FW) and activated sludge (AS) as co-substrates for improving biogas production through anaerobic digestion (AD). The research aims to determine the optimal FW-AS ratio and its application in an anaerobic sequencing batch reactor (SBR) while evaluating the impact of various organic loading rates (OLR): 10g, 25g, and 50g VS L −1 d −1 on biogas production and microbial composition. Dark fermentation at the AD experiments revealed a 25% increase in biogas and methane production. In AD-microbial electrolytic cell (MEC) system, the optimized H-MEC system demonstrated a yield of 92% of the biomethane obtained with more than 90% of CO 2 conversion from the AD system.